The variations in the spontaneous combustion characteristics of coal during primary and secondary oxidation under varying particle sizes - Peitao Zhu; Zhenya Zhang; Zihao Chai; Yaxian Yu (Scientific Reports)
Abstract The coal spontaneous combustion (CSC) in the goaf of a coal mine poses a significant safety hazard. This study investigates the gas production characteristics, apparent activation energy, and limiting parameters of coal samples with varying particle sizes during the low-temperature oxidation stage under both primary and secondary oxidation conditions through a temperature-programmed experiment. The results indicate that smaller particle size leads to higher rates of O2 consumption, CO generation, and heat release intensity in coal samples; The O2 consumption rate, CO generation rate, and heat release intensity during the secondary oxidation of coal samples are relatively high in the initial stage of the experiment. However, in the later stage of the experiment, there is a reversal in these parameters; the selection of the most appropriate model from the 22 commonly observed reaction kinetics mechanism functions revealed that the apparent activation energy of the coal sample decreases during secondary oxidation compared to primary oxidation within the temperature range of 80℃ to 130℃. However, a reversal occurs between temperatures of 140℃ and 170℃, indicating that secondary oxidation initially enhances the low-temperature oxidation characteristics but weakens them in later stages; The various particle sizes under both primary and secondary oxidation conditions significantly influence the limit parameters of CSC, with secondary oxidation being more prone to inducing SC of coal in goaf compared to primary oxidation.